Family experiences of bipolar disorder : the ups, the downs and the bits in between - Aiken, Cara, 1964- (Jessica Kingsley Publishers, 2010)
Bipolar disorder can be a devastating illness, seriously affecting not only the person with bipolar but also their children, partner, parents, family and friends. While most people are familiar with the terms 'manic depressive' and 'bipolar disorder', there remains a lack of real understanding about the illness and many sufferers and their families can feel helpless, alone and misunderstood. "Family Experiences of Bipolar Disorder" is a personal and honest account of bipolar disorder. The author Cara Aiken has lived with bipolar for 10 years, and in this book she gathers together her.